Dimethylethanolamine Decreases Epileptiform Activity in Acute Human Hippocampal Slices in vitro - Kraus, Larissa; Hetsch, Florian; Schneider, Ulf C.; Radbruch, Helena; Holtkamp, Martin; Meier, Jochen C.; Fidzinski, Pawel (Frontiers in Molecular Neuroscience, 2019)
Temporal lobe epilepsy (TLE) is the most common form of focal epilepsy with about 30% of patients developing pharmacoresistance. These patients continue to suffer from seizures despite polytherapy with antiepileptic drugs (AEDs) and have an increased risk for premature death, thus requiring further efforts for the development of new antiepileptic therapies. The molecule dimethylethanolamine (DMEA) has been tested as a potential treatment in various neurological diseases, albeit the functional mechanism of action was never fully understood. In this study, we investigated the effects of DMEA on neuronal activity in single-cell recordings of primary neuronal cultures. DMEA decreased the frequency of spontaneous synaptic events in a concentration-dependent manner with no apparent effect on resting membrane potential (RMP) or action potential (AP) threshold. We further tested whether DMEA can exert antiepileptic effects in human brain tissue ex vivo. We analyzed the effect of DMEA on epileptiform activity in the CA1 region of the resected hippocampus of TLE patients in vitro by recording extracellular field potentials in the pyramidal cell layer. Epileptiform burst activity in resected hippocampal tissue from TLE patients remained stable over several hours and was pharmacologically suppressed by lacosamide, demonstrating the applicability of our platform to test antiepileptic efficacy. Similar to lacosamide, DMEA also suppressed epileptiform activity in the majority of samples, albeit with variable interindividual effects. In conclusion, DMEA might present a new approach for treatment in pharmacoresistant TLE and further studies will be required to identify its exact mechanism of action and the involved molecular targets.